Cleavage Referendums: Ideological Decisions and Transformational Political Change - Reidy, Theresa (2025)
Referendum use has been increasing around the world. In some cases, referendum devices are incorporated into the institutional architecture of the state while in many others, referendums are used in an, and often consultative manner, to determine positions on contentious and divisive political questions. Many of the divisive referendum questions are what we term “cleavage referendums” in this thematic issue. These referendums ask questions that draw from underlying cleavages or fault lines in politics. Voting in these referendums will often exhibit first‐order effects, as voters make decisions that align with their fundamental values and beliefs. The articles in this issue make three important contributions to enrich existing work on referendums: The first contribution lies in the development of new conceptual models for analysing referendums, such as new forms of classifying cleavage referendums, presenting a predictive model for the outcomes of referendum votes, and documenting and applying methodological approaches and frameworks that can provide the foundations for further future comparative work. The second contribution builds on the burgeoning literature that sits at the intersection of deliberative and direct democracy. In this sense, the articles interrogate examples of deliberative and participatory innovations in combination with referendum votes, while also examining their further potential, especially in one of the most contentious referendum contexts, secession. Finally, the role of cleavage structures in shaping voter decision‐making is explored thoroughly in comparative analyses and single case studies.